A Metabiography of Alexander von Humboldt - Rupke, Nicolaas A. (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2006)
AbstractThe author's recently published monograph on Alexander von Humboldt describes the multiple images of this great cultural icon. The book is a metabiographical study that shows how from the middle of the nineteenth century to the present day Humboldt has served as a nucleus of crystallisation for a variety of successive socio-political ideologies, each producing its own distinctive representation of him. The historiographical implications of this biographical diversity are profound and support current attempts to understand historical scholarship in terms of memory cultures.
Keywords: Metabiography